ISTI: At The Cutting Edge Of Sport Science - Straub, W. F.; Spino, M. P. (Today´s Chiropractor, 2000)
After observing the problems that elite athletes were experiencing during the 1996 Atlanta Olympic Games, Dr. Sid E. Williams, founder and president of Life University, established the International Sport Training Institute (ISTI). A former athlete and recent inductee into Georgia Tech`s Football Hall of Fame, Dr. Williams wanted ISTI to become a leading center for international sport science research and dissemination of information about training methods of elite athletes. Vision, a Williams trademark, became the central focus of ISTI`s research arm. More specifically, he instructed ISTI leaders to identify the most pressing problems associated with elite athletic performance and then try to solve them. His Dynamic Essentials of Lasting Peak Performance (DELPP) program, a mental skills training regimen for athletes, became the centerpiece of ISTI. Under the leadership of Michael P. Spino, ISTI researchers began a series of investigations of important aspects of athletic training - such as the effects of heat and humidity, psychological preparation and the ramifications of jet lag - and how they affect performance. In cooperation with the Australian Institute of Sport, athletes were monitored during their psychological acclimation as they prepared for the 1996 Olympic Games. Results indicated that acclimation occurs quite rapidly, but a window of approximately three weeks is needed for athletes to adjust well.